An annotated checklist of fruit flies (Diptera: Tephritidae) of Iran - Namin, Saeed Mohamadzade; Korneyev, Valery A. (Zootaxa, 2018)
Based on data published before August 31, 2017 a checklist of the family Tephritidae (Diptera) includes 152 species and subspecies in 41 genera and three subfamilies. The list includes the distribution by province and the most important references on the nomenclature, existing keys, catalogues, original descriptions and redescriptions for the species recorded from Iran.